Efficiency and effectiveness of the Janashakthi (Bank) Programme in the Hambantota District of Sri Lanka - Lionel, W. P. A.; Lund, Ragnhild; Wickramanayake, B.W.E.; Routray, Jayant Kumar; Swedish International Development Authority ( SIDA) (Bangkok : Asian Institute of Technology, 1994)
This study was undertaken with a view to probing efficiency and effectiveness of the Janashakthi (Bank) Programme of the Hambantota District of Sri Lanka, as a credit-based participatory development programme, and exploring its replicability as an alternative poverty alleviation strategy. The focus of the study is on the performance of the Janashakthi Bank and the socio-economic upliftment of the beneficiaries, as resulting from the bank's performance over the past four years (1990-94) since its inception, as a people's venture. The beneficiaries are share- holders, asset- builders, decision- makers and the borrowers of the bank. The findings of the research show that the programme has performed at a considerably high level of efficiency and effectiveness, and that the beneficiaries, while improving their position of investment, income, savings and acquisition of assets, have been able to alleviate certain economic problems inherent in the i r poverty as well as contributing to its perpetuation. Alleviation of some of the prevalent and major problems associated with poverty, and the social advancement attained by the beneficiaries, imply greater empowerment, holding out promise of alleviation of poverty of all beneficiaries, in future. Moreover, the findings also bear out the potential for sustainability of the programme, supporting its replicability. However, the programme seems to need further strengthening and boosting in order to be capable of lifting its beneficiaries from the position of poverty in the near future, solving their social and economic problems adequately, and enhancing their capacity for control ling factors affecting their lives. The recommendations made herein are directed towards that end.
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1994
Keywords: Poverty -- Research -- Sri Lanka -- Hambantota